HUBUNGAN KUALITAS PELAYANAN DAN KUALITAS PRODUK DENGAN KEPUASAN PELANGGAN PT. TAMAN KAMPUNG ARTIS RENTAL BROADCASTING EQUIPMENT DAN SHOOTING LOCATION - Tuty Mutiah (Universitas Bina Sarana Informatika, 2017)
His study aimed to analyze the relationship Quality of Service and Quality of Products With Customer Satisfaction PT. Taman Kampong Artist Rental Broadcasting Equipment and Shooting Location. This research was carried out in different places to get the respondent. While the product quality is the ability of a product to meet and satisfy the needs of a customer who is buying or using goods or services. In this study using the method of quantitative research. A questionnaires distributed to 34 customers PT. Taman Kampung Artist (PT. TKA) known as the Hometown of the artist, is an Entertainment that is committed and consistently to be the most comprehensive in Indonesia. Results of the study showed that the quality of service and product quality are jointly able to explain the relationship of customer satisfaction just of 0.049 or very low. And the rest is affected by other variables not examined. Keywords: quality of service, product quality, Customer Satification, PT. Taman Kampung Artis Rental Broadcasting Equipment Dan Shooting Location